2019
DOI: 10.1101/866814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

d-Lysergic acid diethylamide has major potential as a cognitive enhancer

Abstract: Psychedelic agonists of serotonin receptors induce neural plasticity and synaptogenesis, but their potential to enhance learning remains uncharted. Here we show that a single dose of d-LSD, a potent serotonergic agonist, increased novel object preference in young and adult rats several days after treatment. d-LSD alone did not increase preference in old animals, but could rescue it to young levels when followed by a 6-day exposure to enriched environment (EE).Mass spectrometry-based proteomics in human brain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(43 reference statements)
1
2
0
Order By: Relevance
“…BDNF-induced glutamate release has been shown to decrease following chronic restraint stress, together with glucocorticoid receptor expression [52]. In line with the current findings, LSD increased synaptic plasticity in brain organoids, an effect accompanied by increased expression of proteins involved in synaptogenesis and plasticity, such as synaptophysin, glutamate metabotropic receptor 7, and synaptic vesicle glycoprotein 2A [62]. LSD shares with antidepressants not only the capacity to increase the density of apical dendritic spines in the mPFC [57], which is hypothesized to endure antidepressant effects but also the capacity to potentiate the 5-HT neurotransmission.…”
Section: Discussionsupporting
confidence: 89%
“…BDNF-induced glutamate release has been shown to decrease following chronic restraint stress, together with glucocorticoid receptor expression [52]. In line with the current findings, LSD increased synaptic plasticity in brain organoids, an effect accompanied by increased expression of proteins involved in synaptogenesis and plasticity, such as synaptophysin, glutamate metabotropic receptor 7, and synaptic vesicle glycoprotein 2A [62]. LSD shares with antidepressants not only the capacity to increase the density of apical dendritic spines in the mPFC [57], which is hypothesized to endure antidepressant effects but also the capacity to potentiate the 5-HT neurotransmission.…”
Section: Discussionsupporting
confidence: 89%
“…In rat models, 5HT2A-R activation with mid-dose psilocybin (0.13 mg/kg) enhances both prospective and retrospective learning with lesser effects at low-dose (0.06 mg/kg; Buchborn et al, 2014 ; Cini et al, 2019 ). Consecutive daily dosing diminished benefits, and older rodents learning was enhanced by an enriched environment (Buchborn et al, 2014 ).…”
Section: Longer-term Effectsmentioning
confidence: 99%
“…The presence of psychedelics in the early human diet may have also favored positive selection for exaggerated cortical plasticity – which apparently is a uniquely human derivation ( Krubitzer, 2009 ) – and for the expansion of key functional networks involved in the enhancement of cognitive functions in humans compared to other primate species. Through their agonist action at 5-HT 2A receptors, psychedelics elevate synaptic efficacy and neuroplasticity ( Ly et al, 2018 ) and functionally modulate the activity and connectivity of the frontoparietal network and the DMN ( Carhart-Harris and Friston, 2019 ; Vollenweider and Preller, 2020 ), enhancing (potentially in the long-term) cognitive functioning ( Cini et al, 2019 ) and sociality ( Preller and Vollenweider, 2019 ). It has also been shown that psychedelic effects can reduce symptoms of autism ( Sigafoos et al, 2007 ) and mimic certain aspects of psychosis ( Carhart-Harris et al, 2016a ).…”
Section: Discussionmentioning
confidence: 99%